Breakup length and liquid splatter characteristics of air-assisted water jets. (May 2016) - Trainer, Daniel
Highlights: The breakup length and liquid splatter onset of air-assisted jets are investigated. Bubble size and number density are found to affect breakup length. Jet breakup length is predicted using the volumetric void fraction. Jet breakup length and the liquid splatter onset point are found to be related. Abstract: The breakup length and liquid splatter onset point of circular, air-assisted liquid water jets are experimentally and visually investigated over a range of parameters important to optimal impinging jet heat transfer. Liquid-only and air-assisted jets in the Rayleigh and first wind-induced breakup regimes are observed. The void fraction is used as a measure of bubble size and number density for air-assisted jets having a bubbly flow and it is found that increasing void fraction tends to decrease jet breakup length. It is hypothesized that bubbles may cause radial velocity components in the jet, leading to reduced breakup lengths. Linear jet stability analysis is used to show that dimensionless jet breakup length is related to the liquid Weber number, Ohnesorge number, and void fraction. The liquid splatter onset point is also measured experimentally. Liquid splatter is shown to occur in drop impingement and jet impingement splatter modes. The liquid splatter onset point and jet breakup length are shown to be related when splatter occurs in the drop impingement splatter mode.